Ohkawa Kazushi, Differential Structure and Agriculture: essays on dualistic growth. Economic Research Series No. 13. The Institute of Economic Research Hitotsubashi University. Tokyo, 1972. - T., L. (Estudios de Asia y África, 1976)
-